2023
DOI: 10.1002/csc2.20862
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Response of intercropping coffee (Coffea arabica L.) with banana (Musa spp.) on yield, yield components, and quality of coffee

Abstract: The coffee plant (Coffea arabica L.) is thought to have begun as an understory tree species in Ethiopia's northeastern high rain forests. Bananas (Musa spp.) are commonly intercropped with coffee to provide shade as well as food and money. However, the effect of this practice on coffee production is little known, hence the present study was initiated with the objective of evaluating the effect of intercropping coffee with banana on the yield and quality of both crops. The experiment was carried out using matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Moreover, intercropping optimizes soil nutrient management and fortifies crop nutrient supply, ultimately augmenting plant biomass ( Zhang et al., 2016 ; Eusun et al., 2022 ; Lu et al., 2024 ). Conventionally, a higher proportion of the main crop correlates with increased yield ( Tehulie and Nigatie, 2023 ). However, the present study revealed no significant differences in C. esculentus , alfalfa, and soybean yields among treatments with varying intercropping proportions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, intercropping optimizes soil nutrient management and fortifies crop nutrient supply, ultimately augmenting plant biomass ( Zhang et al., 2016 ; Eusun et al., 2022 ; Lu et al., 2024 ). Conventionally, a higher proportion of the main crop correlates with increased yield ( Tehulie and Nigatie, 2023 ). However, the present study revealed no significant differences in C. esculentus , alfalfa, and soybean yields among treatments with varying intercropping proportions.…”
Section: Discussionmentioning
confidence: 99%